Effect of Date of Sowing on Foraging Behaviour of Honeybees in Seed Crop of Sunflower Hybrid APSH-11 - R.N. YADAV; S.N. SINHA; N.C. SINGHAL (Seed Research, 2026)
Maximum honeybee activity was recorded in February sown crop followed by January and December. Its activity was highly influenced by air temperature and humidity. Among honeybees, Apis mellifera was the most abundant species. Its frequency was lower in December (11.15) sown crop, followed by January (19.32) and February (21.25) sowings. In the early morning (08:00 hr) its proportion is lower (13.12) than rest of the day (18.09 to 18.53). The highest mean (7.31) honeybee activity was recorded at 10:00 hr. Proportion of pollen gathering bees was more in December (3.32) sown crop than those sown in January (1.59) and February (1.94), whereas the nectar collecting bees were maximum in February (14.45) sown crop, followed by January (13.23) and December (6.68), indicating a shift in the behaviour of honeybees from pollen gathering in December to nectar collection in February.